Open access to scientific literature and research data: a window of opportunity for Latin America - Molfino, Rosario (2012)
The advance that the international open access movement has had in the last decade may seem to suggest that we are witnessing an important change in the model of scientific communication. This paper introduces the fundamental concepts of this movement, and in turn tries to measure the impact it has had in Latin America based on the development of different strategies.